ผลกระทบของการปรับเปลี่ยนระบบป้องกันที่มีต่อการประเมินแรงดันตกชั่วขณะในระบบไฟฟ้ากำลัง - มนทิรา จันเทรมะ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This thesis presents the effect of protection system modification on voltage dip assessment in a power system due to faults. A method of fault positioning and a developed computer program are adopted to assess voltage dip for both magnitude and duration at the point of interest while there is a fault in power systems base on actual data of MEA s substation. The results are used to evaluate in voltage dip coordination charts compared by each type of protection system which are differed by a duration of fault clearing and/or a magnitude of voltage dip. As a result, the consideration of effect of protection system modification on voltage dip is one of the solutions to reduce the effect of voltage dip on power system